Challenges for palliative care in times of COVID-19: a scoping review - Lourenço, Marisa; Gomes, Tânia; Araujo, Fátima; Ventura, Filipa; Silva, Rosa (Frontiers in Public Health, 2024)
Many of the essential practices in palliative care (PC) had to be adapted to the COVID-19 pandemic. This global spread of the infectious respiratory disease, caused by SARS-CoV-2, created unprecedented obstacles. The aim of this research was to comprehensively assess the experiences and perceptions of healthcare professionals, individuals, and families in palliative and end-of-life situations during the COVID-19 pandemic. Methods: A scoping review was conducted using the databases CINAHL Complete, MEDLINE, Scopus, SciELO, Cochrane Central Register of Controlled Trials, Psychology and Behavioral Sciences, MEDIClatina, and Portugal's Open Access Scientific Repository. The review followed the JBI® methodological approach for scoping reviews. Results: Out of the initially identified 999 articles, 22 studies were included for analysis. The deprivation of relationships due to the safety protocols required to control the spread of COVID-19 was a universally perceived experience by healthcare professionals, individuals in PC, and their families. Social isolation, with significant psychological impact, including depersonalization and despair, was among the most frequently reported experiences by individuals in palliative situation. Despite healthcare professionals' efforts to mitigate the lack of relationships, the families of these individuals emphasized the irreplaceability of in-person bedside contact.